Evolution of NAO and AMO strength and cyclicity derived from a 3-ka varve-thickness record from Iceland - Olafsdottir, K.; Geirsdottir, A.; Miller, Gifford; Larsen, D. (Elsevier, 2013)
A 3000-year varve-thickness record from Hvítárvatn, a glacier-dominated lake in central Iceland, preserves inter-annual variations in the delivery of glacially eroded sediment to the lake. The first-order lowfrequency trend in varve thickness reflects increased glacial erosion through the Late Holocene, reaching a peak during the Little Ice Age (LIA). Superimposed on this trend are large inter-annual to decadal fluctuations in varve thickness that we suggest reflect variability in climate parameters that determine the efficiency of the fluvial transport system to deliver glacially eroded sediment to the lake each year. We use spectral analysis to test whether regular high-frequency cyclicity in varve thickness exists in the 3-ka record after removing the low-frequency variability. Spectral analyses from three sediment cores recovered from the lake show essentially the same periods of 2.8e3.4, 13, 35e40 and 85e93, for the overlapping w900-year period. Additionally, cycles of 55, 130 and 290 years are found in the spectrum for the 3000-year record that do not show up in the spectra for the shorter cores. Some of these cycles show similar variability to those of the North Atlantic Oscillation (NAO) and Atlantic Multidecadal Oscillation (AMO). This relationship is supported by a significant correlation between varve thickness and both the NAO (precipitation) and AMO (summer temperature) indices over the 180-year instrumental period. NAO cyclicities (2e15 years) are weakly expressed in the first half of the record, increase between 600 and 1000 AD, decrease in strength during medieval time, and are most strongly expressed between 1300 AD and the early 20th century. AMO cyclicities (50 to 130 years) are also relatively weak in the first half of the record, becoming quite strong between 600 and 1000 AD and again between 1100 and 1500 AD, but are essentially absent through the peak of the LIA, between 1500 and 1900 AD, a time when strong cyclicities of about 35 years appear.